Trainee experiences in a specialist neuropsychiatry training position. (February 2020) - Rego, Thomas; Eratne, Dhamidhu; Walterfang, Mark; Velakoulis, Dennis
Objective: To explore trainee perceptions of a specialist training post in neuropsychiatry. Method: Of 47 past trainees who had worked in the Neuropsychiatry Unit at the Royal Melbourne Hospital during the period 1993 to 2017, 32 (68%) completed an online questionnaire including 10 questions, 4 of which asked for open-ended responses. Results: Most trainees provided positive feedback about their past experiences working on the unit, including utilizing knowledge and experience in their current practice. To an open question about how working on the unit influenced career choices 21/31 (68%) responses were positive. The remaining 10 responses highlighted areas of improvement for the trainee positions. Conclusions: The specialty training position within neuropsychiatry was very popular among past trainees, the majority of whom endorsed using the knowledge learnt in neuropsychiatry in their current practice and recommended work on the unit to future trainees.